WHEAT LANDRACES OF TURKEY - Karagö, Z. Alptekin (Emirates Journal of Food and Agriculture, 2015)
Turkey falls within Vavilov's Center of origin and harbors large genetic diversity of several economicallyimportant crop species. Wild crop relative, such as wild einkorn, wild emmer, wild barley, wild oats, wild ryeand their respective domesticated forms, in addition to a multitude of other crop species, have been cultivatedfor millennia in several parts of Turkey, but especially in the northern part of the Fertile Crescent. Turkishfarmers developed landraces from these crops; however, these landraces and the indigenous knowledge gainedover many generations are being lost due to several anthropogenic and other factors. Landraces of wheat andother major and minor crops still play an important role in the livelihood of small scale farmers in Turkey. Thispaper reviews and contrasts the current status of Turkey's main wheat landraces with their past; and suggestsspecific strategies for their maintenance.